_ | y = 3x, { | x + y = 4, = |y = 3x, { | x = 4 - y, = | y = 3 • (4 - y), { | x = 4 - y, = | y = 12 - 3y, { | x = 4 - y, = | y + 3y = 12, { | x = 4 - y, = | 4y = 12, { | x = 4 - y, = | y = 12 : 4, { | x = 4 - y, = | y = 3, { | x = 4 - y, = | y = 3, { | x = 1. - ответ: (1;3).
x+3x=4
x=1
y=3*1
y=3
ответ
(x,y)=(1,3)
| y = 3x,
{
| x + y = 4,
=
|y = 3x,
{
| x = 4 - y,
=
| y = 3 • (4 - y),
{
| x = 4 - y,
=
| y = 12 - 3y,
{
| x = 4 - y,
=
| y + 3y = 12,
{
| x = 4 - y,
=
| 4y = 12,
{
| x = 4 - y,
=
| y = 12 : 4,
{
| x = 4 - y,
=
| y = 3,
{
| x = 4 - y,
=
| y = 3,
{
| x = 1.
-
ответ: (1;3).